Composite improved regenerated cement stabilized macadam mixture and preparation method thereof

By using composite improved recycled cement stabilized gravel mixture in roadbed materials, using hydrophobic modified nanoclay and modified hollow polypropylene fibers, the temperature difference resistance of the mixture is improved, and the traditional cement stabilized gravel mixture is solved. Inadequate performance problem in environments with large temperature difference between day and night.

CN119462026AInactive Publication Date: 2025-02-18THE 2ND ENG CO LTD OF CHINA RAILWAY URBAN CONSTR GRP

Patent Information

Application Number
CN202510056299.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional cement-stabilized gravel mixtures have poor temperature resistance when used as roadbed materials in an environment with large temperature difference between day and night.

Method used

Using composite improved recycled cement stabilized gravel mixture, including natural aggregates, recycled aggregates, cement, water and modified hollow polypropylene fibers, the nanoclay is hydrophobicly modified to combine it with the hydrated product to enhance mechanics and prevent moisture evaporation and loss of moisture by modifying fibers, improving anti-freeze and anti-dry shrinkage properties.

Benefits of technology

Under standard conditions and large temperature difference environment, the performance of composite improved recycled cement stable gravel mixture complies with national standards and is suitable for areas with large temperature difference between day and night, with wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of roadbed materials, in particular to a composite improved regenerated cement stabilized macadam mixture and a preparation method thereof. The composite improved regenerated cement stabilized macadam mixture is prepared from the following raw materials in parts by weight: 45 to 50 parts of natural aggregate, 45 to 50 parts of regenerated aggregate, 5 to 6 parts of cement, 14 to 16 parts of water and 0.8 to 1 part of modified hollow polypropylene fiber. The composite improved regenerated cement stabilized macadam mixture disclosed by the invention is cured under standard conditions or in a large-temperature-difference environment, all performances of the composite improved regenerated cement stabilized macadam mixture meet national standards, and the composite improved regenerated cement stabilized macadam mixture has a wide application prospect in the field of roadbed materials, especially in regions with large day and night temperature difference.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of roadbed materials, and in particular to a composite improved recycled cement stabilized crushed stone mixture and a preparation method thereof. Background Art

[0002] Patent technical document CN117658555A is a cement-stabilized gravel mixture of fully recycled brick-concrete aggregate and a preparation method thereof. The cement-stabilized gravel mixture of fully recycled brick-concrete aggregate of the invention comprises the following components in parts by weight: 100 parts of aggregate, 4.5-5.5 parts of cement and 13.4-15.6 parts of water, and 0-0.3 parts of modified rubber powder. The invention improves the utilization rate of recycled brick-concrete aggregate, opens up a new way to discard rubber powder, and is beneficial to improving the crack resistance of cement-stabilized gravel base. And the use of 100% recycled brick-concrete aggregate greatly reduces the project cost and is beneficial to environmental protection. Patent technology document CN109987898A A cement-stabilized crushed stone mixture and its preparation process, the cement-stabilized crushed stone mixture of the invention includes the following components by weight: 4-5 parts of silicate cement, 30-45 parts of new aggregate, 20-25 parts of recycled aggregate, 28-36 parts of stone chips, 4-8 parts of polypropylene fiber, 10-12 parts of wollastonite powder, 0.3-0.5 parts of aluminum titanate, 5-10 parts of expansion agent, 4-8 parts of water. The cement-stabilized crushed stone in the invention has good flexural tensile strength, is not easy to produce shrinkage cracks, and has a high overall quality, so that the road as a whole maintains good stability and is not easy to be damaged.

[0003] The above patents all provide a cement-stabilized crushed stone mixture, which has the advantages of crack resistance and shrinkage resistance. However, when it is used in an environment with a large temperature difference between day and night, especially in the northwest of my country, its performance is seriously affected. Summary of the invention

[0004] In view of this, the purpose of the present invention is to propose a composite improved recycled cement-stabilized crushed stone mixture and a preparation method thereof, so as to solve the problem that the traditional cement-stabilized crushed stone mixture has poor temperature difference resistance as a roadbed material in an environment with a large temperature difference between day and night.

[0005] Based on the above purpose, the present invention provides a composite improved recycled cement stabilized gravel mixture, comprising the following raw materials in parts by weight: 45-50 parts of natural aggregate, 45-50 parts of recycled aggregate, 5-6 parts of cement, 14-16 parts of water, and 0.8-1 part of modified hollow polypropylene fiber; The preparation steps of the modified hollow polypropylene fiber are as follows: S1: drying the nanoclay, dispersing it in deionized water, adding hydrochloric acid and nitric acid, stirring at room temperature at a speed of 1000 rpm for 6 h, filtering, drying, and obtaining activated nanoclay; S2: In a nitrogen atmosphere, the activated nanoclay is dispersed in anhydrous ethanol, maintained at 60-70°C for 2 h, and then 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane is added dropwise, fully shaken, and heated for 4-5 h, filtered, dried, washed, and dried to obtain hydrophobic nanoclay; S3: putting polypropylene and hydrophobized nanoclay into a high-speed mixer for high-speed mixing, then injecting a coupling agent, continuing mixing, and then melt-granulating in a twin-screw extruder at 140-160° C. to obtain polypropylene / clay composite particles, and then preparing modified hollow polypropylene fibers by melt spinning; The usage ratio of the nanoclay, deionized water, hydrochloric acid and nitric acid in step S1 is 4-6g:200-300ml:2-3ml:2-3ml; The ratio of activated nanoclay, anhydrous ethanol and 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane used in step S2 is 4-5g:200-300ml:2-4ml; The weight ratio of the polypropylene to the hydrophobized nanoclay in step S3 is 93-97:3-7; The melt spinning parameters in step S3 are as follows: a spinning temperature of 170-230°C; nitrogen is used as the cavity fluid with a flow rate of 0.01-0.1 L / min; the cooling process first adopts short-distance air cooling and then solvent cooling, and after cooling, it is wound into a hollow fiber with a winding speed of 140-420 m / min, and it is sheared into 15-20 mm to obtain a modified hollow polypropylene fiber.

[0006] Preferably, the particle size of the nanoclay in step S1 is 50-100 nm.

[0007] Preferably, the concentration of hydrochloric acid in step S1 is 1 mol / L; Preferably, the concentration of nitric acid in step S1 is 2 mol / L.

[0008] Preferably, the polypropylene in step S3 is drawing-grade homopolymer polypropylene with a melt index of 0.3-4 g / 10 min.

[0009] Preferably, in step S3, the air temperature is 5-30° C., and the air cooling length is 0.5-3 m.

[0010] Preferably, the solvent temperature in step S3 is 5-60°C.

[0011] Preferably, the coupling agent in step S3 is an aluminate coupling agent.

[0012] Furthermore, the present invention also provides a method for preparing a composite improved recycled cement stabilized gravel mixture, the steps of which are as follows: (1) Mix the natural aggregate and the recycled aggregate, stir evenly, add half of the water, stir evenly, then add P42.5 grade Portland cement, stir evenly, add the remaining water, stir evenly, and obtain a mixture; (2) Add modified hollow polypropylene fibers into the mixture, stir and mix evenly to obtain a composite improved recycled cement stabilized gravel mixture.

[0013] Beneficial effects of the present invention: The composite improved recycled cement stabilized gravel mixture of the present invention meets national standards in all aspects of performance, whether it is cured under standard conditions or in an environment with a large temperature difference. It has broad application prospects in the field of roadbed materials, especially in areas with a large temperature difference between day and night.

[0014] The composite improved recycled cement-stabilized crushed stone mixture of the present invention hydrophobically modifies nanoclay so that long hydrophobic chains can be combined with hydration products, thereby improving the mechanical properties of the mixture. At the same time, the long hydrophobic chains can enter the internal pores along with the modified hollow fibers to hinder the evaporation and loss of water, thereby improving the antifreeze and anti-shrinkage properties of the mixture.

[0015] The composite improved recycled cement stabilized crushed stone mixture of the present invention uses modified hollow fibers formed by a composite of polypropylene and hydrophobic nano clay, so that the mechanical strength, antifreeze and anti-shrinkage properties of the mixture are improved. DETAILED DESCRIPTION

[0016] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0017] Example 1: A composite improved recycled cement stabilized gravel mixture, the specific preparation steps are as follows: (1) 4 g of nanoclay was placed in a drying oven and baked at 80 °C until completely dry, then mixed with 200 ml of deionized water, 2 ml of 1 mol / L hydrochloric acid and 2 ml of 2 mol / L nitric acid, stirred at 1000 rpm for 6 h at room temperature, filtered, dried, and activated nanoclay was obtained; in a nitrogen atmosphere, 4 g of activated nanoclay was mixed with 200 ml of anhydrous ethanol, kept at 60 °C for 2 h, then 2 ml of 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane was dropped, fully shaken, continued to heat for 4 h, filtered, and dried at a constant temperature at 80 °C under vacuum conditions, washed with anhydrous ethanol for 3 times, and dried to obtain hydrophobic nanoclay; (2) 93 g of polypropylene and 7 g of hydrophobized nanoclay were placed in a high-speed mixer and mixed at high speed for 2 min, then an aluminate coupling agent was injected and the mixture was mixed for 5 min. The mixture was then melt-granulated at 140 °C in a twin-screw extruder to obtain polypropylene / clay composite particles. The modified hollow polypropylene fiber was then prepared by melt spinning. The polypropylene / clay composite particles were melt-extruded and spun through a spinning machine at a spinning temperature of 170 °C. Nitrogen was used as the cavity fluid at a flow rate of 0.01 L / min. The cooling process first adopted short-distance air cooling at an air temperature of 5 °C and an air cooling length of 0.5 m, and then solvent cooling at a solvent temperature of 5 °C. After cooling, the fibers were wound into hollow fibers at a winding speed of 140 m / min and cut into 15 mm to obtain modified hollow polypropylene fibers. (3) 4.5 kg of natural aggregate and 4.5 kg of recycled aggregate were mixed and stirred evenly, and then half of the water was added and stirred evenly. Subsequently, 0.5 kg of P42.5 grade Portland cement was added and stirred evenly. The remaining water was added and stirred evenly to obtain a mixture. Finally, 80 g of modified hollow polypropylene fiber was added to the mixture and stirred evenly to obtain a composite improved recycled cement stabilized gravel mixture.

[0018] Example 2: A composite improved recycled cement stabilized gravel mixture, the specific preparation steps are as follows: (1) 5 g of nanoclay was placed in a drying oven and baked at 80 °C until completely dry, then mixed with 250 ml of deionized water, 2.5 ml of 1 mol / L hydrochloric acid and 2.5 ml of 2 mol / L nitric acid, stirred at 1000 rpm for 6 h at room temperature, filtered, dried, and activated nanoclay was obtained; under a nitrogen atmosphere, 4.5 g of activated nanoclay was mixed with 250 ml of anhydrous ethanol, kept at 65 °C for 2 h, then 3 ml of 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane was dropped, fully shaken, continued to heat for 5 h, filtered, and dried at a constant temperature under vacuum conditions at 80 °C, washed with anhydrous ethanol for 3 times, and dried to obtain hydrophobic nanoclay; (2) 95 g of polypropylene and 5 g of hydrophobized nanoclay were placed in a high-speed mixer and mixed at high speed for 2 min, then an aluminate coupling agent was injected and the mixture was continued for 5 min, and then the mixture was melt-granulated at 150 °C in a twin-screw extruder to obtain polypropylene / clay composite particles, and then the modified hollow polypropylene fiber was prepared by melt spinning. The polypropylene / clay composite particles were melt-extruded and spun through a spinning machine at a spinning temperature of 200 °C; nitrogen was used as the cavity fluid at a flow rate of 0.05 L / min; the cooling process first adopted short-distance air cooling at an air temperature of 15 °C and an air cooling length of 2 m, and then solvent cooling at a solvent temperature of 30 °C was adopted. After cooling, the fibers were wound into hollow fibers at a winding speed of 220 m / min, and the fibers were sheared into 18 mm to obtain modified hollow polypropylene fibers; (3) 4.8 kg of natural aggregate and 4.8 kg of recycled aggregate were mixed and stirred evenly, and then half of the water was added and stirred evenly. Subsequently, 0.55 kg of P42.5 grade Portland cement was added and stirred evenly. The remaining water was added and stirred evenly to obtain a mixture. Finally, 95 g of modified hollow polypropylene fiber was added to the mixture and stirred evenly to obtain a composite improved recycled cement stabilized gravel mixture.

[0019] Example 3: A composite improved recycled cement stabilized gravel mixture, the specific preparation steps are as follows: (1) 6 g of nanoclay was placed in a drying oven and baked at 80 °C until completely dry, then mixed with 300 ml of deionized water, 3 ml of 1 mol / L hydrochloric acid and 3 ml of 2 mol / L nitric acid, stirred at 1000 rpm for 6 h at room temperature, filtered, dried, and activated nanoclay was obtained; under a nitrogen atmosphere, 5 g of activated nanoclay was mixed with 300 ml of anhydrous ethanol, kept at 70 °C for 2 h, then 4 ml of 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane was dropped, fully shaken, continued to heat for 5 h, filtered, and dried at a constant temperature at 80 °C under vacuum conditions, washed with anhydrous ethanol for 3 times, and dried to obtain hydrophobic nanoclay; (2) 97 g of polypropylene and 3 g of hydrophobized nanoclay were placed in a high-speed mixer and mixed at high speed for 2 min, then an aluminate coupling agent was injected and the mixing was continued for 5 min, followed by melt granulation at 160 °C in a twin-screw extruder to obtain polypropylene / clay composite particles, and then the modified hollow polypropylene fiber was prepared by melt spinning. The polypropylene / clay composite particles were melt extruded and spun through a spinning machine at a spinning temperature of 230 °C; nitrogen was used as the cavity fluid at a flow rate of 0.1 L / min; the cooling process first adopted short-distance air cooling at an air temperature of 30 °C and an air cooling length of 3 m, and then solvent cooling at a solvent temperature of 60 °C was adopted. After cooling, the fibers were wound into hollow fibers at a winding speed of 420 m / min, and the fibers were sheared into 20 mm to obtain modified hollow polypropylene fibers; (3) 5 kg of natural aggregate and 5 kg of recycled aggregate were mixed and stirred evenly, and then half of the water was added and stirred evenly. Subsequently, 0.6 kg of P42.5 grade Portland cement was added and stirred evenly. The remaining water was added and stirred evenly to obtain a mixture. Finally, 100 g of modified hollow polypropylene fiber was added to the mixture and stirred evenly to obtain a composite improved recycled cement stabilized gravel mixture.

[0020] Comparative Example 1: A composite improved recycled cement stabilized gravel mixture, the specific preparation steps are as follows: (1) 95 g of polypropylene and 5 g of nanoclay were placed in a high-speed mixer and mixed at high speed for 2 min, then an aluminate coupling agent was injected and the mixture was continued for 5 min, and then the mixture was melt-granulated at 150 °C in a twin-screw extruder to obtain polypropylene / clay composite particles, and then the modified hollow polypropylene fiber was prepared by melt spinning. The polypropylene / clay composite particles were melt-extruded and spun by a spinning machine at a spinning temperature of 200 °C; nitrogen was used as the cavity fluid at a flow rate of 0.05 L / min; the cooling process first adopted short-distance air cooling at an air temperature of 15 °C and an air cooling length of 2 m, and then solvent cooling at a solvent temperature of 30 °C was adopted. After cooling, the fibers were wound into hollow fibers at a winding speed of 220 m / min, and the fibers were sheared into 18 mm to obtain modified hollow polypropylene fibers; (2) 4.8 kg of natural aggregate and 4.8 kg of recycled aggregate were mixed and stirred evenly, and then half of the water was added and stirred evenly. Subsequently, 0.55 kg of P42.5 grade Portland cement was added and stirred evenly. The remaining water was added and stirred evenly to obtain a mixture. Finally, 95 g of modified hollow polypropylene fiber was added to the mixture and stirred evenly to obtain a composite improved recycled cement stabilized gravel mixture.

[0021] Comparative Example 2: A composite improved recycled cement stabilized gravel mixture, the specific preparation steps are as follows: (1) 5 g of nanoclay was placed in a drying oven and baked at 80 °C until completely dry, then mixed with 250 ml of deionized water, 2.5 ml of 1 mol / L hydrochloric acid and 2.5 ml of 2 mol / L nitric acid, stirred at 1000 rpm for 6 h at room temperature, filtered, dried, and activated nanoclay was obtained; under a nitrogen atmosphere, 4.5 g of activated nanoclay was mixed with 250 ml of anhydrous ethanol, kept at 65 °C for 2 h, then 3 ml of 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane was dropped, fully shaken, continued to heat for 5 h, filtered, and dried at a constant temperature under vacuum conditions at 80 °C, washed with anhydrous ethanol for 3 times, and dried to obtain hydrophobic nanoclay; (2) 95 g of polypropylene was placed in a high-speed mixer and mixed at high speed for 2 min, then an aluminate coupling agent was injected and the mixing was continued for 5 min, and then the polypropylene pellets were melt-granulated at 150 ° C in a twin-screw extruder to obtain polypropylene pellets, and then the hollow polypropylene fiber was prepared by melt spinning. The polypropylene pellets were melt-extruded and spun through a spinning machine at a spinning temperature of 200 ° C; nitrogen was used as the cavity fluid at a flow rate of 0.05 L / min; the cooling process first adopted short-distance air cooling, the air temperature was 15 ° C, the air cooling length was 2 m, and then solvent cooling was adopted, the solvent temperature was 30 ° C, and after cooling, it was wound into a hollow fiber at a winding speed of 220 m / min, and it was cut into 18 mm to obtain a hollow polypropylene fiber; (3) 4.8 kg of natural aggregate and 4.8 kg of recycled aggregate were mixed and stirred evenly, and then half of the water was added and stirred evenly. Subsequently, 0.55 kg of P42.5 grade Portland cement was added and stirred evenly. The remaining water was added and stirred evenly to obtain a mixture. Finally, 95 g of hollow polypropylene fiber and 5 g of hydrophobic nanoclay were added to the mixture and stirred evenly to obtain a composite improved recycled cement stabilized gravel mixture.

[0022] Comparative Example 3: A composite improved recycled cement stabilized gravel mixture, the specific preparation steps are as follows: (1) 95 g of polypropylene was placed in a high-speed mixer and mixed at high speed for 2 minutes, and then an aluminate coupling agent was injected and mixed for 5 minutes. Then, the mixture was melt-granulated at 150°C in a twin-screw extruder to obtain polypropylene particles. Then, hollow polypropylene fibers were prepared by melt spinning. The polypropylene particles were melt-extruded and spun through a spinning machine at a spinning temperature of 200°C. Nitrogen was used as the cavity fluid at a flow rate of 0.05 L / min. During the cooling process, short-distance air cooling was first used, with an air temperature of 15°C and an air cooling length of 2 m. Then, solvent cooling was used, with a solvent temperature of 30°C. After cooling, the fibers were wound into hollow fibers at a winding speed of 220 m / min, and the fibers were sheared into 18 mm to obtain hollow polypropylene fibers. (3) 4.8 kg of natural aggregate and 4.8 kg of recycled aggregate were mixed and stirred evenly, and then half of the water was added and stirred evenly. Subsequently, 0.55 kg of P42.5 grade Portland cement was added and stirred evenly. The remaining water was added and stirred evenly to obtain a mixture. Finally, 95 g of hollow polypropylene fiber was added to the mixture and stirred evenly to obtain a composite improved recycled cement stabilized gravel mixture.

[0023] Comparative Example 4: A composite improved recycled cement stabilized gravel mixture, the specific preparation steps are as follows: (1) 5 g of nanoclay was placed in a drying oven and baked at 80 °C until completely dry, then mixed with 250 ml of deionized water, 2.5 ml of 1 mol / L hydrochloric acid and 2.5 ml of 2 mol / L nitric acid, stirred at 1000 rpm for 6 h at room temperature, filtered, dried, and activated nanoclay was obtained; under a nitrogen atmosphere, 4.5 g of activated nanoclay was mixed with 250 ml of anhydrous ethanol, kept at 65 °C for 2 h, then 3 ml of 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane was dropped, fully shaken, continued to heat for 5 h, filtered, and dried at a constant temperature under vacuum conditions at 80 °C, washed with anhydrous ethanol for 3 times, and dried to obtain hydrophobic nanoclay; (2) 85 g of polypropylene and 15 g of hydrophobized nanoclay were placed in a high-speed mixer and mixed at high speed for 2 min, then an aluminate coupling agent was injected and the mixing was continued for 5 min, and then the mixture was melt-granulated at 150 °C in a twin-screw extruder to obtain polypropylene / clay composite particles, and then the modified hollow polypropylene fiber was prepared by melt spinning. The polypropylene / clay composite particles were melt-extruded and spun through a spinning machine at a spinning temperature of 200 °C; nitrogen was used as the cavity fluid at a flow rate of 0.05 L / min; the cooling process first adopted short-distance air cooling at an air temperature of 15 °C and an air cooling length of 2 m, and then solvent cooling at a solvent temperature of 30 °C was adopted. After cooling, the fibers were wound into hollow fibers at a winding speed of 220 m / min, and the fibers were sheared into 18 mm to obtain modified hollow polypropylene fibers; (3) 4.8 kg of natural aggregate and 4.8 kg of recycled aggregate were mixed and stirred evenly, and then half of the water was added and stirred evenly. Subsequently, 0.55 kg of P42.5 grade Portland cement was added and stirred evenly. The remaining water was added and stirred evenly to obtain a mixture. Finally, 95 g of modified hollow polypropylene fiber was added to the mixture and stirred evenly to obtain a composite improved recycled cement stabilized gravel mixture.

[0024] Performance Testing Standard curing environment: curing is carried out according to the "Test Procedures for Stabilized Materials of Inorganic Binders for Highway Engineering", and the samples obtained in the examples and comparative examples are transferred to a standard curing room for constant temperature and humidity curing, with a temperature of 20±2°C and a humidity of ≥95%; Large temperature difference curing environment: The curing temperature range is 5-30℃, the humidity is 65%, and the specific temperature changes are as follows: the temperature starts at 20℃, then cools down at a rate of 5℃ / h. When it cools down to 5℃, keep it for 7h, then heat it to 30℃ at 5℃ / h, keep it for 7h, and then cool it down to 20℃ at 5℃ / h. This is one cycle, i.e. 1d.

[0025] The mixed materials in the test were all cylindrical mixed materials with a size of Φ150mm×150mm. After demoulding, the mixed materials were placed in a curing room for curing. The test was conducted after 24h of water immersion curing one day before the predetermined age. Unconfined compressive strength: After the mixture is cured for 28 days, it is tested according to the Test Procedure for Stabilized Materials with Inorganic Binders for Highway Engineering (JTG E51-2009); Splitting tensile strength: After the mixture is cured for 28 days, the test is carried out according to the "Testing Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering" (JTG E51-2009); Frost resistance: After curing the mixture for 28 days, five freeze-thaw cycles were performed and tested according to the Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering (JTG E51-2009); Shrinkage performance: After curing the mixture (100mm×100mm×400mm, beam-type mixture) for 7 days, the mixture was tested according to the Test Procedure for Stabilized Materials of Inorganic Binders for Highway Engineering (JTG E51-2009); Table 1 Standard curing performance test results

[0026] Table 2 Large temperature difference curing performance test

[0027] Data analysis: The composite improved recycled cement stabilized gravel mixture of the present invention meets national standards in all aspects of performance, whether it is cured under standard conditions or in an environment with a large temperature difference. It has broad application prospects in the field of roadbed materials, especially in areas with a large temperature difference between day and night.

[0028] It can be seen from the data of Example 2 and Comparative Example 1 in the table that the present invention hydrophobically modifies the nanoclay. On the one hand, the long hydrophobic chains on its surface can produce a tighter combination with the hydration product, and at the same time can form physical entanglement with each other, so that the compressive strength and tensile strength of the mixture are improved to a certain extent. On the other hand, the long hydrophobic chains can enter the pores on the surface of the aggregate along with the fibers, and while blocking the penetration of external moisture, they can also block the channels for moisture loss, thereby reducing the evaporation loss of moisture in the mixture, thereby improving the antifreeze and anti-shrinkage properties of the mixture.

[0029] It can be seen from the data of Example 2 and Comparative Examples 2 and 3 in the table that the present invention adds nanoclay, and the nanoclay can react physically / chemically with the hydration product to enhance the binding force between the raw materials. At the same time, it can fill part of the gaps, reduce the penetration of water, and improve the mechanical strength / antifreeze and anti-shrinkage performance of the mixture. The modified hollow composite fiber formed by polypropylene fiber and hydrophobic nanoclay can further improve the mechanical properties and antifreeze / anti-shrinkage performance of the mixture. This is mainly due to the addition of composite fibers relative to polypropylene fibers and hydrophobic nanoclays. The composite fibers can be more evenly dispersed inside the mixture, and can better block the internal gaps and pores. At the same time, the hydration performance of the mixture will not be affected by uneven dispersion. In addition, the modified hollow polypropylene fiber has both the toughness of the hollow fiber and the excellent mechanical properties of the fiber due to the composite of nanoclay.

[0030] It can be seen from the data of Example 2 and Comparative Example 4 in the table that when the content of nanoclay in the modified hollow polypropylene fiber is too much, the mechanical properties of the mixture are improved to a certain extent, but its anti-freeze and anti-shrinkage properties are significantly reduced. This is probably because when the content of nanoclay is too much, it is not evenly dispersed inside the modified hollow polypropylene fiber, and agglomeration may occur, thereby destroying the structure of the modified hollow polypropylene fiber, thereby introducing more gaps and channels into the mixture.

[0031] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A composite improved recycled cement stabilized gravel mixture, characterized in that: The raw materials include the following parts by weight: 45-50 parts of natural aggregate, 45-50 parts of recycled aggregate, 5-6 parts of cement, 14-16 parts of water, and 0.8-1 parts of modified hollow polypropylene fiber; The preparation steps of the modified hollow polypropylene fiber are as follows: S1: drying the nanoclay, dispersing it in deionized water, adding hydrochloric acid and nitric acid, stirring at room temperature at a speed of 1000 rpm for 6 h, filtering, drying, and obtaining activated nanoclay; S2: In a nitrogen atmosphere, the activated nanoclay is dispersed in anhydrous ethanol, maintained at 60-70°C for 2 h, and then 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane is added dropwise, fully shaken, and heated for 4-5 h, filtered, dried, washed, and dried to obtain hydrophobic nanoclay; S3: putting polypropylene and hydrophobized nanoclay into a high-speed mixer for high-speed mixing, then injecting a coupling agent, continuing mixing, and then melt-granulating in a twin-screw extruder at 140-160° C. to obtain polypropylene / clay composite particles, and then preparing modified hollow polypropylene fibers by melt spinning; The usage ratio of the nanoclay, deionized water, hydrochloric acid and nitric acid in step S1 is 4-6g:200-300ml:2-3ml:2-3ml; The ratio of activated nanoclay, anhydrous ethanol and 1H,1H,2H,2H-perfluorooctylmethyldimethoxysilane used in step S2 is 4-5g:200-300ml:2-4ml; The weight ratio of the polypropylene to the hydrophobized nanoclay in step S3 is 93-97:3-7; The melt spinning parameters in step S3 are as follows: a spinning temperature of 170-230°C; nitrogen is used as the cavity fluid with a flow rate of 0.01-0.1 L / min; the cooling process first adopts short-distance air cooling and then solvent cooling, and after cooling, it is wound into a hollow fiber with a winding speed of 140-420 m / min, and it is sheared into 15-20 mm to obtain a modified hollow polypropylene fiber.

2. The composite improved recycled cement stabilized gravel mixture according to claim 1, characterized in that: The natural aggregate is formed by crushing natural rocks, and the recycled aggregate is recycled brick-concrete aggregate, wherein the weight ratio of brick aggregate to concrete aggregate is 1-2:3-4.

3. The composite improved recycled cement stabilized gravel mixture according to claim 1, characterized in that: The recycled aggregate and natural aggregate are divided into four grades according to particle size: 0-5mm: 5-10mm: 10-20mm: 20-30mm, and the composition ratio of each grade of aggregate is 0-5mm: 5-10mm: 10-20mm: 20-30mm = 30%: 22%: 15%: 33%.

4. The composite improved recycled cement stabilized gravel mixture according to claim 1, characterized in that: The cement is P42.5 grade silicate cement.

5. The composite improved recycled cement stabilized gravel mixture according to claim 1, characterized in that: The particle size of the nanoclay in step S1 is 50-100 nm.

6. The composite improved recycled cement stabilized gravel mixture according to claim 1, characterized in that: In step S1, the concentration of hydrochloric acid is 1 mol / L, and the concentration of nitric acid is 2 mol / L.

7. The composite improved recycled cement stabilized gravel mixture according to claim 1, characterized in that: The polypropylene in step S3 is drawing grade homopolymer polypropylene, and the melt index is between 0.3-4 g / 10 min.

8. The composite improved recycled cement stabilized gravel mixture according to claim 1, characterized in that: In step S3, the air temperature is 5-30°C, the air cooling length is 0.5-3m; the solvent temperature is 5-60°C.

9. A method for preparing the composite improved recycled cement stabilized crushed stone mixture according to any one of claims 1 to 8, characterized in that: Here are the steps: (1) Mix the natural aggregate and the recycled aggregate, stir evenly, add half of the water, stir evenly, then add P42.5 grade Portland cement, stir evenly, add the remaining water, stir evenly, and obtain a mixture; (2) Add modified hollow polypropylene fibers into the mixture, stir and mix evenly to obtain a composite improved recycled cement stabilized gravel mixture.

Citation Information

Patent Citations

  • Cement stabilized macadam mixture of full-recycled brick-mixed aggregate and preparation method of cement stabilized macadam mixture

    CN117658555A

  • Cement stabilized macadam mixture and preparation process thereof

    CN109987898A

  • Anti-crack concrete and preparation method thereof

    CN118619627A

Cited By

  • Low-carbon crack-resistant fully-regenerated stabilized macadam mixture based on building demolition solid waste and preparation method of low-carbon crack-resistant fully-regenerated stabilized macadam mixture

    CN121591456A